You are on page 1of 2

Z ∞

F (s) = L{ f (t)} = e−st f (t) dt
0

L
f (t) −−−−−−−−−→ F (s)
L−1
f (t) ←−−−−−−−−−− F (s)

´

´ objeto f (t)
Funcion ´ imagen F (s)
Funcion

1. a f 1 (t) + b f 2 (t) aF1 (s) + bF2 (s)
1 s

2. f ( at) aF a

3. e at f (t) F (s − a)
(
f (t − a), si t > a
4. g(t) = e−as F (s)
0, si t < a
5. f 0 (t) sF (s) − f (0)

6. f 00 (t) s2 F ( s ) − s f (0) − f 0 (0)

7. f (n) (t) s n F ( s ) − s n −1 f (0 ) − s n −2 f 0 (0 ) − · · · − f ( n −1) (0 )

8. t f (t) − F 0 (s)

9. t2 f (t) F 00 (s)

10. tn f (t) (−1)n F (n) (s)
Rt F (s)
11. 0 f (u) du s
Rt
12. f (t) ∗ g(t) = 0 f (u) g(t − u) du F (s) G (s)
f (t) R∞ f (t)
13. t s F ( u ) du, si l´ ım
t →0 t
existe.
 R
1 K −st
14. f (t) = f (t + K ) 1−e−sK 0 e f (t) dt
R∞
15. 0 f (t) dt F (0)

16. l´ım F (s) = 0
s→∞
17. l´ım sF (s) = l´ım f (t), si los l´ımites existen.
s→∞ t →0
18.l´ım sF (s) = l´ım f (t), si los l´ımites existen.
s →0 t→∞
Z ∞
F (s) = L{ f (t)} = e−st f (t) dt
0

L
f (t) −−−−−−−−−→ F (s)
L−1
f (t) ←−−−−−−−−−− F (s)

´ objeto f (t)
Funcion ´ imagen F (s)
Funcion
Γ ( n +1)
tn s n +1
1
e at s− a
n!
tn e at ( s − a ) n +1
,n = 0, 1, 2, 3, · · ·
a
sin( at) s2 + a2
s
cos( at) s2 + a2
a
ebt sin( at) ( s − b )2 + a2
s−b
ebt cos( at) ( s − b )2 + a2
1
e at − e−at a

sinh( at) = 2 s2 − a2
1
e at + e−at s

cosh( at) = 2 s2 − a2
a
ebt sinh( at) ( s − b )2 − a2
s−b
ebt cosh( at) ( s − b )2 − a2
ebt −e at 1
b− a (s− a)(s−b)
, a 6= b
bebt − ae at s
b− a (s− a)(s−b)
, a 6= b
2as
t sin( at) ( s2 + a2 )2
s2 − a2
t cos( at) ( s2 + a2 )2

j0 ( at) √ 1
s2 + a2
√ n
s2 + a2 − s
jn ( at) √
a n s2 + a2

2